Effect of Business Risk, Profitability, and Investment Decisions on Capital Structure - Ati Retna Sari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The usage of both foreign and domestic capital is balanced in capital structure. When it comes to managing business finances, capital is crucial. The purpose of this study is to investigate how business risk, profitability, and investment choices affect the capital structure of automobile businesses that are listed between 2019 and 2021 on the Indonesia Stock Exchange (IDX). Purposive sampling, a technique for selecting object samples based on predetermined criteria, is the approach employed. Up to ten automakers are listed on the IDX, which is the number of samples according on the criterion. Multiple regression tests are used by the data analysis tool. The tiny number of automotive businesses in this study is its restriction, which leads to less than ideal outcomes.